Dampak Relokasi Pasar Terhadap Kondisi Sosial Ekonomi Pedagang Pasar Tente Kecamatan Woha Kabupaten Bima - M Junaidi; Ramayanto Ramayanto; Nurlailatul Nurlailatul (Universitas Muhammadiyah Mataram, 2018)
The market is one of the most important institutions in economic institutions. The functioning of market institutions as economic institutions that drive economic life can not be separated from the activities undertaken by traders and buyers. The formulation of the problem is, How the Socio-Economic Impact on Tente Market relocation. This study aims to describe the Impact of Market Relocation to Socio-Economic Conditions of Tente Market Traders. This research uses descriptive qualitative method. The results of this study indicate that, there is a social change, which technically traders and locations trade from the old market move to new markets. In this market shift raises the impact, ie social and economic impacts such as manifestations, with the impact of manifestations, the impact behind them is the latency impact experienced by traders after the relocation of the market. And less intennya interaction that exists between old traders and new traders. The social impacts that arise are the lack of social systems, interactions and personal relationships. The emerging economic impact of declining income after occupying the new Tente market.